On buoyancy driven mixing by volumetric microwave energy deposition. (July 2015) - Wachtor, A.J.; Mocko, V.; Jebrail, F.F.; Andrews, M.J.
Abstract: Investigation of buoyancy driven mixing by volumetric energy deposition is of particular interest to inertial confinement fusion research. This contribution describes a new microwave facility and an experiment to study buoyancy driven mixing of miscible fluids by volumetric energy deposition. A light weakly-polar fluid initially rested on top of a heavier and higher polarity fluid. As the fluid system was subjected to microwave radiation, less microwave energy was deposited into the weakly-polar fluid than the higher polarity fluid; thus, the bottom fluid was preferentially heated, and its density decreased due to thermal expansion. With continued microwave heating, the density of the bottom fluid dropped below the density of the upper fluid, creating a Rayleigh–Taylor unstable configuration, and, subsequently, buoyancy driven mixing. The miscible pair of toluene and tetrahydrofuran was chosen for the volumetric energy deposition experiments presented. Initially, single fluid microwave heating experiments, for which the source term in the heat equation was varied by variations in the fluid volume, were performed to provide calibration of a mathematical model. The model provided a prediction of the neutral stability point of the system, which facilitated experimental design and understanding. Measurements of the mixing layer width from this two-fluid mixing experiment are compared with results from a self-similar analysis of the governing equations.